Antioxidant Effect of Lactobacillus fermentum CQPC04-Fermented Soy Milk on D-Galactose-Induced Oxidative Aging Mice - Zhou, Xianrong; Du, Hang-hang; Jiang, Meiqing; Zhou, Chaolekang; Deng, Yuhan; Long, Xingyao; Zhao, Xin (Frontiers in Nutrition, 2021)
The aim of this study is to evaluate the changes in soy isoflavones and peptides in soy milk after lactic acid bacterial fermentation, and explore the positive effects of fermented soy milk on an oxidative aging mouse model induced with D-galactose. We found that free soybean isoflavones and peptides increased after soy milk was fermented by Lactobacillus fermentum CQPC04. The in vivo results indicated that L. fermentum CQPC04-fermented soy milk enhanced the organ index of the liver and spleen, and improved the pathological morphology of the liver, spleen, and skin. L. fermentum CQPC04-fermented soy milk increased the enzymatic activity of total superoxide dismutase (T-SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), increased glutathione (GSH), but decreased the levels of malondialdehyde (MDA) and nitric oxide (NO) in serum, liver, and brain tissues of oxidative aging mice. The above mentioned fermented soy milk also increased the levels of collagen I (Col I), collagen III (Col III), and hyaluronic acid (HA), and decreased the levels of advanced glycation End products (AGEs) and hydrogen peroxide (H2O2). The RT-qPCR results showed that L. fermentum CQPC04-fermented soy milk upregulated the mRNA expression of nuclear factor erythroid 2⁃related factor (Nrf2), heme oxygenase-1 (HMOX1), quinone oxido-reductase 1 (Nqo1), neuronal nitric oxide synthase (NOS1), endothelial nitric oxide synthase (NOS3), Cu/Zn–superoxide dismutase (Cu/Zn-SOD), Mn–superoxide dismutase (Mn-SOD), and CAT, but downregulated the expression of inducible nitric oxide synthase (NOS2) and glutamate cysteine ligase modifier subunit (Gclm) in liver and spleen tissues. Lastly, the fermented soy milk also increased the gene expression of Cu/Zn-SOD, Mn-SOD, CAT, GSH-Px, matrix metalloproteinases 1 (TIMP1), and matrix metalloproteinases 2 (TIMP2), and decreased the expression of matrix metalloproteinase 2 (MMP2) and matrix metalloproteinase 9 (MMP9) in skin tissue. In conclusion, L. fermentum CQPC04-fermented soy milk was able to satisfactorily delay oxidative aging effects, and its mechanism may be related to the increase in free soy isoflavones and peptides.